ANALISIS ETIKA BISNIS PRODUKSI DAN PEMASARAN TERHADAP PELANGGARAN PRINSIP ETIKA LINGKUNGAN HIDUP - Maghfiroh, Efi Laila; Alam, Alingga Damar; Rosiawan, Rizky Wahyudha (Media Mahardhika, 2026)
This study aims to comprehensively analyze the application of business ethics in production and marketing activities and identify ethical violations that impact the environment using the Systematic Literature Review (SLR) approach. Guided by the PRISMA method, by analyzing twenty scientific articles published between 2020 and 2025 that are related to the topics of business ethics, production, marketing, and environmental desires. The results of the study indicate that corporate reputation and environmental desires are strongly influenced by business ethics such as honesty, social responsibility, transparency, and desires that have a significant influence on corporate reputation and environmental sustainability. Frequent violations found include advertising manipulation, the use of non-environmentally friendly raw materials, and production practices that damage the ecosystem. The impact of these violations includes a decrease in public trust and corporate reputation. This study emphasizes the importance of integrating ethical values in corporate policies to achieve a balance between economic profit and social and environmental responsibility. This research contributes to strengthening business actors’ awareness and becomes the basis for developing sustainable business policies in the future.